(untitled) (Indian Journal of Animal Production and Management, 2024)
Precision Dairy Farming (PDF) is a new emerging field of sensor technology with the related algorithms, interfaces, and wide applications that defines modern cattle farming. This paper gives an insight into the presently available technologies that can be implemented in farms of various sizes whereby a large unit of animals can be still be observed with individual attention. There are a large number of technologies with varying levels of applications. Hence this paper classifies these technologies from the perspective of Livestock Production and Management into four pillars viz., breeding, feeding, weeding and heeding. Each of these pillars is explained with the latest available information as applicable to Indian conditions. Nevertheless, countless entrepreneurs have already adopted these technologies. This is just an attempt to update the readers about the latest developments in this field and the potential application at dairy farms for improved milk production.